Analisis Keterbatasan Penggunaan Media Pembelajaran Dan Pengaruhnya Terhadap Minat Belajar Siswa Kelas 2 SD N Krebet - Nara Puspitaningrum, Mareeta; Heru Purnomo (Universitas Muhammadiyah Bangka Belitung, 2025)
This research analyzes the limitations the use of learning media and its impact on the learning interest of second-grade students at SD Negeri Krebet. Finding the causes of these restrictions and how they affect student motivation is the aim of the study. A descriptive qualitative approach is used in the study. Interviews, observations, and documentation were used to gather data. The research results show that the limitations of learning media, such as the lack of access to modern teaching aids, significantly reduce student enthusiasm and engagement. The recommendations proposed include enhancing teacher training and investing in learning media facilities by schools to improve the quality of education.